Faktor Penyebab Terjadinya Perdagangan Ilegal HCFC-22 antara India dan Cina - Rosyada, Amrina; Windiani, Reni; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to explain the causes of illegal trade of HCFC-22 between India and China in 2013-2014 from India’s side. This research used qualitative methods, with compliance theory by Ronald B. Mitchell to analyze the causes of the case. There are some result of this research. First, this reasearch found out that the illegal trade of HCFC-22 is a low-low relations. Second, the illegal trade was caused by the incapacity, seen from the limited ability of Indian goverment to fulfill the necessary of alternative chemichal substitution to HCFC-22 and the limited ability of Indian society to afford the stuff with alternative chemichal due tue economic and environmental condition.